The use of information in the world economy: globalization trends - Vdovichena, Olha; Vidomenko, Oksana; Tkachuk (Stakhurska), Svitlana; Zhuzhukina, Nataliia; Lukianykhina, Olena (My University, 2022)
Актуальність досліджуваної проблеми полягає в сучасному розвитку світової економіки в умовах глобалізації. Оскільки інформація зробила прорив у розвитку світової економіки, стала її новим багатством, вбачається доцільним дослідження сучасних тенденцій її використання. Інформація використовується в усіх галузях економіки. Він має потужність і динамічний характер. Інформація здатна як покращувати економіку, так і руйнувати її, покращувати довкілля, а також забруднювати його, впливати на політичний та економічний розвиток країни. Використання інформації допомагає країнам синхронізуватися зі світовою економікою з метою її глобалізації. Раціональне використання інформації, правильний підхід і технологічні можливості сприяють розвитку циркулярної економіки, високопрофесійна трудова міграція, адаптація до кліматичних змін та пандемії, формування економічної свідомості населення через ЗМІ. Метою даного дослідження було виявлення та характеристика основних глобалізаційних тенденцій використання інформації. Для досягнення цієї мети було проаналізовано економічну, соціологічну, технологічну та наукову літературу 2022 року. Основні результати. За допомогою емпіричних досліджень та аналізу наукової літератури та даних було виявлено наступні глобалізаційні тенденції у використанні інформації: зміна характеру та способу використання інформації населенням світу, використання інформації для розвитку циркулярної економіки. , використання баз даних, обмін інформацією та використання інформації засобами масової інформації. The relevance of the investigated problem is the modern development of the world economy in the conditions of globalization. Because the information caused a breakthrough in developmen of the world economy, became its new wealth, it was seen that it is appropriate to research modern trends of its use. Information is used in all branches of the economy. It has power and a dynamic character. Information is capable of improving the economy, as well as destroying it, improving the environment, as well as polluting it, and influencing the political and economical development of the country. The use of information helps countries synchronize with the world economy in order to globalize it. The rational use of information, the right approach and technological capabilities contribute to the development of a circular economy, highly professional labor migration, adaptation to the climate change and the pandemic, and the formation of the economic consciousness of the population through mass media. The purpose of this study was to identify and characterize the main globalization trends of the use of information. To achieve this goal, economic, sociological, technological and scientific literature of 2022 was analyzed. The main results. With the help of empirical studies and analysis of scientific literature and data, the following globalization trends in the use of information were identified: change in the nature and method of information use by the global population, use of information for the development of a circular economy, use of databases, information exchange and use of information by mass media. The practical meaning of this research is the application of findings about the latest trends in the use of information for enterprises striving to enter the global market in further scientific research.
Keywords: economical globaliztion; information in the circular economy; informational society; globalization trends; informational economy; кафедра економіки і права